Thrombus removal prior to recanalization in vein graft occlusion intervention. (February 2019) - Fung, Raymond Chi-Yan; Jim, Man-Hong
A saphenous vein graft chronic total occlusion intervention is uncommonly performed, partly due to the high risk of distal embolization. We described a strategy in which after successful wiring of a saphenous vein graft chronic total occlusion, balloon dilatation was performed to create a blind sac within the lesion, followed by aspiration thrombectomy to remove all the dislodged debris. Thereafter, balloon dilatation and stenting were safely performed in the distal occluded segment, to achieve complete recanalization.